Serina Gredler (Gastropoda, Stylommatophora: Enidae), the continuous-peristomed mountain snails endemic to the eastern slope of the Qinghai-Xizang Plateau - Wu, Min; Xu, Qin (Zootaxa, 2013)
In this paper we initiate a taxonomic review of the genus Serina Gredler, endemic to the eastern slope of the Qinghai- Xizang Plateau, namely S Gansu, SW Sichuan, SE Xizang Autonomous Region and N Yunnan of China. We describe the genital anatomy for some species and the shell morphology for all known species: Serina belae (Hilber), S. cathaica Gredler, S. egressa Sturany, S. prostoma (Ancey), S. ser Gredler, S. subser Gredler, S. soluta (Möllendorff) and S. vincentii (Gredler). Based on the re-evaluation of both shell and genitalian differentiations we prefer to classify the taxon egressa as a separate species rather than a subspecies of S. ser. In our study we come to the conclusion that S. soluta inflata Yen and S. soluta stenochila (Möllendorff) should be regarded as synonyms of S. soluta due to the insufficient differentiation among them. Buliminus (Holcauchen) tubios Annandale, Bulimus prostoma leucochila Ancey and Serina deqenensis Chen, Zhou and Luo were conspecific with Serina prostoma and that Serina sobrina (Preston) was conspecific with Clausiliopsis szechenyi (Böttger). We propose a new species Serina denticulata n. sp. from the Southern Gansu Plateau. Furthermore we discuss the phylogenetic relationship among the genera Serina, Clausiliopsis Möllendorff, Pupopsis Gredler, and Pupinidius Möllendorff based on the morphological data from twelve relevant species.